Secondary battery

By using hard-segment monomers and soft-segment monomer polymer binders and carbonate electrolytes in lithium-ion secondary batteries, the compatibility between the binders and electrolytes was optimized, the binder swelling problem was solved, and the electrochemical performance and safety of the batteries were improved.

CN121460682APending Publication Date: 2026-02-03ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511590577.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2026-02-03

AI Technical Summary

Technical Problem

Traditional adhesive materials are prone to swelling in lithium-ion secondary batteries, which leads to unstable connection between electrode materials and current collectors, affecting the cycle life, capacity retention and safety of the secondary battery.

Method used

A polymer synthesized from hard segment monomers and soft segment monomers is used as the negative electrode binder, and carbonate substances are used in the electrolyte. By adjusting the ratio of the mass content of soft segment monomers to the mass content of carbonate substances, the compatibility between the binder and the electrolyte is optimized, a stable SEI film is formed, and swelling is reduced.

Benefits of technology

It improves the electrochemical performance of secondary batteries, extends cycle life, improves capacity retention and safety, prevents binder corrosion, and enhances the compatibility between the negative electrode and the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of secondary batteries, and discloses a secondary battery, a negative active layer in a negative plate comprises a negative active material and a negative adhesive, the negative active material comprises a silicon-based material, the negative adhesive comprises a polymer, and the raw material of the polymer comprises a hard segment monomer and a soft segment monomer; the electrolyte comprises carbonic ester substances and lithium salt; on the basis of the total mass of the raw materials of the polymer, the mass content of the soft segment monomer is r%; on the basis of the total mass of the electrolyte, the mass content of the carbonic ester substance is t%; t / r is greater than or equal to 0.234 and less than or equal to 1.770. According to the secondary battery provided by the invention, the chemical structure of the adhesive is optimized and the composition of the electrolyte solution is adjusted, so that the excellent electrochemical performance of the battery is ensured, the swelling effect of the electrolyte on the adhesive is reduced, the cycle life of the battery is prolonged, and the safety of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of secondary batteries, specifically to a secondary battery. Background Technology

[0002] Lithium-ion rechargeable batteries are widely used in modern electronic devices, electric vehicles, and energy storage systems. The adhesive between the electrodes and current collectors in lithium-ion rechargeable batteries is a crucial factor in ensuring the structural integrity and electrochemical performance of the battery. However, traditional adhesive materials are prone to swelling during prolonged use, which can lead to unstable connections between the electrode materials and the current collectors, thereby affecting the cycle life, capacity retention, and safety of the rechargeable battery.

[0003] The swelling phenomenon of adhesives is usually related to the composition of polar solvents in the electrolyte used in secondary batteries. The polar solvents in the electrolyte can interact with the polar groups in the adhesive, causing the electrolyte to penetrate into the adhesive inside the electrode, reducing the bonding performance between the polymer molecules in the adhesive, resulting in volume expansion and increased mass of the adhesive, which in turn leads to a decrease in the performance of the secondary battery. Summary of the Invention

[0004] In view of this, this application provides a secondary battery that aims to effectively reduce the swelling of the binder to a certain extent, thereby optimizing the cycle performance and safety performance of the secondary battery.

[0005] To achieve the above objectives, this application adopts the following solution.

[0006] This invention provides a secondary battery, comprising a negative electrode sheet, a positive electrode sheet, a separator, and an electrolyte. The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least one side surface of the negative electrode current collector. The negative electrode active layer includes a negative electrode active material and a negative electrode binder. The negative electrode active material includes a silicon-based material. The negative electrode adhesive comprises a polymer, and the raw materials of the polymer include hard segment monomers and soft segment monomers; The electrolyte comprises carbonates and lithium salts; Based on the total mass of the raw materials for the polymer, the mass content of the soft segment monomer is r%; Based on the total mass of the electrolyte, the mass content of the carbonate substances is t%; Both satisfy the condition 0.234≤t / r≤1.770.

[0007] In one optional embodiment, the mass content of the hard segment monomer is s%, with s being 39.8~77.8%, based on the total mass of the raw materials of the polymer.

[0008] In one alternative implementation, the hard segment monomer satisfies at least one of the following conditions: a. The hard segment monomer comprises a polyisocyanate, the polyisocyanate comprising at least one aliphatic ring, wherein the number of carbon atoms in the aliphatic ring n1 ≥ 5; b. The two end groups of the hard segment monomer include isocyanate groups, and the hard segment monomer does not contain any other unsaturated groups other than isocyanate groups.

[0009] In one alternative implementation, r is 13 to 47.

[0010] In one alternative implementation, the soft segment monomer satisfies at least one of the following conditions: A. The soft segment monomer has hydroxyl-terminated end groups; B. The number of carbon atoms n2 in the main chain of the soft segment monomer is 3 or more, preferably 5 or more; C. The main chain of the soft segment monomer does not contain any of the following: ether bonds, ester bonds, or carbon-carbon double bonds; D. The soft segment monomer includes a side chain, wherein the number of repeating units n3 of the side chain is less than 40, the number of carbon atoms in the side chain n4 is greater than or equal to 1, and the end group of the side chain includes at least one of methyl, cyano, and amide groups.

[0011] In one alternative embodiment, the hard segment monomer comprises at least one of 1,4-cyclohexane diisocyanate, isophorone diisocyanate, norbornene diisocyanate, and dicyclohexylmethane diisocyanate.

[0012] In one optional embodiment, the soft segment monomer comprises at least one of 2-methyl-1,5-pentanediol, 2,2-dimethyl-1,3-propanediol, 1,2-hydroxystearic acid derivatives, hydrogenated polyisobutylene glycol, dihydroxy-terminated polyethylene, dihydroxy-terminated hydrogenated polybutadiene, poly(ethylene-CO-1,2-butene) glycol, dihydroxy-terminated polymers of (2-acrylonitrile, 1,3-butadiene), and 6-aminohexanoic acid derivatives.

[0013] In one optional embodiment, the raw materials for the polymer further include a crosslinking agent, a hydrophilic chain extender, and a neutralizing agent; the crosslinking agent comprises at least three hydroxyl groups and has a molecular weight ≤200; the hydrophilic chain extender comprises at least two hydroxyl groups and at least one carboxyl group and has a molecular weight ≤204.

[0014] In one optional embodiment, the bonding surface diameter of the negative electrode adhesive is 10 nm to 1000 nm.

[0015] In one alternative embodiment, the electrolyte satisfies at least one of the following conditions: I. The value of t is 10~40; II. The carbonate substances include at least two of the following: ethylene carbonate, propylene carbonate, diethyl carbonate, methyl ethyl carbonate, dimethyl carbonate, and fluoroethylene carbonate; III. The carbonate substance includes ethylene carbonate, and the mass content of ethylene carbonate is less than 10% based on the total mass of the electrolyte; IV. The electrolyte also includes carboxylic acid esters; V. The electrolyte also includes additives; VI. Based on the total mass of the electrolyte, the mass content of the lithium salt is 11.4% to 24.8%; VII. The lithium salt comprises at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorooxalate borate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorobis(oxalate) phosphate, lithium tetrafluoroborate, lithium bis(oxalate) borate, lithium hexafluoroantimonyate, lithium hexafluoroarsenate, lithium di(pentafluoroethylsulfonyl)imide, and lithium tri(trifluoromethylsulfonyl)methyl, preferably lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.

[0016] In one optional embodiment, the mass content of the carboxylic acid ester is 37% to 70% based on the total mass of the electrolyte.

[0017] In one optional embodiment, the carboxylic acid ester includes at least one of propyl propionate, ethyl propionate, ethyl butyrate, propyl acetate, ethyl acetate, and difluoroethyl acetate.

[0018] In one optional embodiment, the additive content is 2.7% to 10.9% based on the total mass of the electrolyte.

[0019] In an optional embodiment, the additive comprises at least one selected from 1,3-propanesulfonyl lactone, lithium difluorophosphate, vinylene carbonate, ethylene ethylene carbonate, vinyl sulfate, 4-methyl-ethylene sulfate, triargyl propargyl phosphate, 1,3,5-pentanetricarbonyl, 1,2,3-propanetricarbonyl, 1,3,6-hexanetricarbonyl, 1,2,6-hexanetricarbonyl, ethylene glycol di(2-cyanoethyl) ether, diethylene glycol di(2-cyanoethyl) ether, triethylene glycol di(2-cyanoethyl) ether, 1,2,3,4,5-penta(2-cyanoethoxy)pentane, tetraethylene glycol di(2-cyanoethyl) ether, ethylene glycol di(4-cyanobutyl) ether, ethylene glycol (bis)propionitrile ether, and tri(3-cyanopropyl) phosphate.

[0020] In an optional embodiment, based on the total mass of the electrolyte, the mass content of lithium hexafluorophosphate is 10.7% to 16.2%, and the mass content of lithium bis(fluorosulfonyl)imide is 2.9% to 8.7%.

[0021] In an optional embodiment, in the negative electrode active material, the silicon-based material includes silicon element. Based on the total mass of the silicon-based material, the mass content of the silicon element is 35% to 70%.

[0022] In an optional embodiment, the particle size D50 of the silicon-based material is 3 μm to 15 μm.

[0023] In an optional embodiment, the specific surface area of the silicon-based material is 0.5 m ,

[0031] , a ,

[0030] , y ,

[0029] , 2 ,

[0028] , , , ,

[0024] , , , z , , x , , ,

[0027] ,

[0026] ,

[0025] / g to 3 m 2 / g.

[0024] In an optional embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer provided on at least one surface of the positive electrode current collector, and the positive electrode active layer includes positive electrode active material.

[0025] The positive electrode active material includes a positive electrode active material, or includes a positive electrode active material and a coating layer provided on the surface of the positive electrode active material.

[0026] In an optional embodiment, the positive electrode active material includes LiNi x Co y Mn z M a O2, where 0.8 ≤ x ≤ 0.95, 0.01 ≤ y ≤ 0.18, 0.01 ≤ z ≤ 0.18, 0 < a ≤ 0.1, and M includes at least one of Al, Mg, Y, W, B, Zr, Ti, Sr, La, and Nb.

[0027] In an optional embodiment, the coating layer includes a metal oxide.

[0028] In an optional embodiment, the thickness of the coating layer is 10 nm to 50 nm.

[0029] In an optional embodiment, the positive electrode active material includes single crystal particles and / or polycrystal particles.

[0030] In an optional embodiment, the particle size D50 of the positive electrode active material is 1 μm to 15 μm. <00001​​The negative electrode binder for the secondary battery provided in this application is a polymer synthesized from hard-segment monomers and soft-segment monomers. The hard-segment monomers in the polymer raw materials can give the polymer a high glass transition temperature (Tg) and strong mechanical strength. Furthermore, its internal cross-linking structure can improve the chemical and thermal stability of the binder, which helps to prevent the electrolyte solvent or other external factors from corroding the binder, thereby maintaining the long cycle life of the battery. The soft-segment monomers can give the binder better flexibility, allowing the binder to better adapt to the volume changes of the silicon-based material in the negative electrode during charging and discharging, and prevent the binder from breaking or falling off during battery operation. In addition, the functional groups in the soft-segment monomers can also improve the swelling properties of the binder. That is, appropriate soft-segment monomers can improve the affinity between the binder and the electrolyte, and improve the compatibility between the negative electrode and the electrolyte. In other words, the polymer binder of this application, through the synergistic effect of soft-segment and hard-segment monomers, can simultaneously possess the advantages of high mechanical strength, good chemical and thermal stability, and good flexibility. This allows the polymer binder to promote compatibility between the negative electrode and the electrolyte while also helping to prevent corrosion of the binder by factors such as the electrolyte. On the other hand, the electrolyte of the secondary battery provided in this application uses carbonate-based substances as organic solvents. Utilizing the excellent film-forming properties of carbonates, a relatively stable solid electrolyte interphase (SEI) film can be constructed on the surface of the chemically active, volume-changing negative electrode containing silicon-based materials, thereby improving the electrochemical performance of the battery. Meanwhile, to achieve a secondary battery that simultaneously possesses excellent electrochemical performance and low electrolyte swelling rate of the binder, this application further ensures that the mass content r% of the soft segment monomer in the polymer raw material and the mass content t% of the carbonate substances in the electrolyte satisfy the following relationship: 0.234≤t / r≤1.770. This ensures sufficient carbonate substances in the electrolyte to form the SEI film on the surface of the negative electrode, while reducing the penetration of free carbonate substances in the electrolyte into the binder of the negative electrode. This effectively avoids the interaction between carbonate substances and polar groups in the binder, thereby reducing the swelling effect of the negative electrode. While ensuring excellent electrochemical performance of the battery, this reduces the impact of the electrolyte on the bonding effect of the negative electrode binder, thereby improving the safety of the secondary battery, extending the cycle life of the battery, and improving the cycle performance of the battery.

[0032] Additional aspects and advantages of the embodiments of this application will be described and shown in part in the following description, or illustrated by practice of the embodiments of this application. Detailed Implementation

[0033] The following embodiments are provided to better understand this application. However, the following embodiments do not constitute a limitation on the content and scope of protection of this application. Any product that is the same as or similar to this application, derived by anyone under the guidance of this application or by combining the features of this application with other prior art, falls within the scope of protection of this application.

[0034] Unless otherwise specified, all experimental steps or conditions in the examples were performed according to conventional experimental procedures and conditions in the art. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0035] To address the problem in related technologies where polar solvents in the electrolyte cause swelling of the binder in the negative electrode, affecting the bonding effect of the binder and thus impacting the cycle life, capacity retention, and safety of the secondary battery, this application proposes the following solution.

[0036] A secondary battery includes a negative electrode, a positive electrode, a separator, and an electrolyte. The negative electrode includes a negative current collector and a negative active layer disposed on at least one surface of the negative current collector. The negative active layer includes a negative active material and a negative binder, wherein: The negative electrode active material includes silicon-based materials; The negative electrode adhesive comprises a polymer, and the raw materials of the polymer include hard segment monomers and soft segment monomers; The electrolyte comprises carbonates and lithium salts; Based on the total mass of the raw materials for the polymer, the mass content of the soft segment monomer is r%; Based on the total mass of the electrolyte, the mass content of the carbonate substances is t%; Both satisfy the condition 0.234≤t / r≤1.770.

[0037] The negative electrode binder used in this application is a polymer composed of hard-segment monomers and soft-segment monomers. First, the hard-segment monomers in the polymer raw materials can give the polymer a high glass transition temperature (Tg) and strong mechanical strength. Furthermore, its internal cross-linking structure can improve the chemical and thermal stability of the binder, helping to prevent the electrolyte or other external factors from corroding the binder, thereby maintaining the long cycle life of the battery. On the other hand, the soft-segment monomers can lower the glass transition temperature of the polymer, giving the binder better flexibility, allowing the binder to better adapt to the volume changes of the silicon-based material in the negative electrode during charging and discharging, and preventing the binder from breaking or falling off during battery operation. In addition, the functional groups in the soft-segment monomers can also improve the swelling properties of the binder. That is, appropriate soft-segment monomers can improve the affinity between the binder and the electrolyte, and improve the compatibility between the negative electrode and the electrolyte. In other words, the polymer binder of this application, through the synergistic effect of soft segment monomers and hard segment monomers, can simultaneously take into account the advantages of high mechanical strength, good chemical and thermal stability, and good flexibility. Thus, the polymer binder can improve the compatibility between the negative electrode and the electrolyte, while also helping to prevent the electrolyte and other factors from corroding the binder.

[0038] On the other hand, the electrolyte of the secondary battery provided in this application uses carbonates as organic solvents. Utilizing the excellent film-forming properties of carbonates, a relatively stable SEI film can be constructed on the surface of the negative electrode, a chemically active material with large volume changes, thus ensuring excellent electrochemical performance of the secondary battery. However, this application's research found that carbonates are polar solvents with strong dipole moments. They can interact with polar groups (such as carboxyl, amino, or hydroxyl groups) in the binder used in the negative electrode, thus penetrating into the binder and even inserting into the polymer chains. This reduces the interaction forces between polymer chains, lowering the polymer chain bond energy and causing the binder material to swell. When swelling reaches a certain level, the interaction forces of the binder molecular chain bonds further weaken, causing the binder material to dissolve. Therefore, this application further adjusts the softness of the polymer raw materials... The mass content r% of the monomer and the mass content t% of carbonates in the electrolyte satisfy the following relationship: 0.234 ≤ t / r ≤ 1.770. This ensures sufficient carbonates in the electrolyte to form the SEI film on the negative electrode surface. Simultaneously, it reduces the penetration of free carbonates from the electrolyte into the binder in the negative electrode, effectively preventing the interaction between carbonates and polar groups in the binder. This reduces the swelling effect of the negative electrode, thereby improving the safety of the secondary battery, extending its cycle life, and enhancing its cycle performance. Therefore, the secondary battery provided in this application, through the optimization of the chemical structure of the binder and the adjustment of the electrolyte solution composition, works synergistically to ensure excellent electrochemical cycle performance while reducing the swelling effect of the electrolyte on the binder, thus extending the battery's cycle life and improving its capacity retention and safety.

[0039] This application also found that when the ratio of the mass content t% of carbonates to the mass content r% of soft segment monomers (t / r) is less than 0.234, the content of carbonates in the electrolyte is too low relative to the content of soft segment monomers in the polymer. This leads to a decrease in the proportion of film-forming agents in the electrolyte, resulting in insufficient carbonates to participate in the formation of the SEI film in the negative electrode. Consequently, the formed SEI film is loose, porous, and has poor mechanical strength, thus affecting the cycle performance of the battery. Conversely, when the ratio of the mass content t% of carbonates to the mass content r% of soft segment monomers (t / r) is greater than 1.770, ... This means that the content of carbonates in the electrolyte is too high relative to the content of soft segment monomers in the polymer. After the excessive carbonates form a film on the silicon anode and the adhesive surface, the excessive free carbonates in the electrolyte will penetrate into the adhesive and insert into the polymer chains, reducing the interaction force between the polymer chains in the adhesive. This reduces the polymer chain energy and causes the adhesive material to swell, affecting the adhesive strength and adhesion durability. Consequently, the connection between the anode active layer and the current collector becomes unstable, affecting the battery's cycle life, capacity retention, and safety.

[0040] It should be noted that the mass content of carbonates in the electrolyte can be obtained by gas chromatography. The mass content of soft segment monomers in the polymer can be obtained by thermogravimetric analysis. For example, the ratio t / r of the mass content of carbonates (t%) to the mass content of soft segment monomers (r%) can be, for example, 0.234, 0.300, 0.400, 0.500, 0.600, 0.700, 0.800, 0.900, 1.000, 1.100, 1.200, 1.300, 1.400, 1.500, 1.600, 1.700, 1.770, or a value within any range of two of the above values.

[0041] In one optional embodiment, the mass content (s%) of the hard segment monomer is 39.8% to 77.8% based on the total mass of the polymer raw materials. This ensures that the polymer binder has appropriate mechanical strength and flexibility, as well as good chemical and thermal stability. While reducing the erosion of the binder by the electrolyte or other external factors, it can effectively adapt to the volume changes of the silicon-based material in the negative electrode during charging and discharging, and improve the swelling properties of the binder, thereby further improving the overall electrochemical performance of the battery.

[0042] This study found that when the mass content (s%) of hard segment monomers in the polymer is less than 39.8%, the glass transition temperature of the polymer binder is too low, its mechanical strength is low, and its chemical and thermal stability decreases. This makes it unable to effectively prevent the electrolyte solution or other external factors from corroding the binder, resulting in a shortened battery cycle life and decreased cycle performance. Conversely, when the mass content (s%) of hard segment monomers in the polymer raw material is higher than 77.8%, the binder has an excessively high glass transition temperature and mechanical strength, leading to decreased elasticity and toughness. This causes the negative electrode sheet to easily crack and shed powder, making it unable to effectively mitigate the volume change of silicon-based materials in the negative electrode sheet during battery charging and discharging. Furthermore, it leads to poor compatibility between the electrolyte and the negative electrode sheet, further deteriorating the battery's cycle performance.

[0043] It should be noted that the mass content of hard segment monomers in the polymer can be obtained by thermogravimetric analysis-infrared analysis. For example, the mass content s% of hard segment monomers in the polymer can be 39.8%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 77.8%, or a value within any two of the above ranges.

[0044] In one alternative implementation, the hard segment monomer satisfies at least one of the following conditions: a. The hard segment monomer comprises a polyisocyanate, the polyisocyanate comprising at least one aliphatic ring, wherein the number of carbon atoms in the aliphatic ring n1 ≥ 5; b. The two end groups of the hard segment monomer include isocyanate groups, and the hard segment monomer does not contain any other unsaturated groups other than isocyanate groups.

[0045] The polyisocyanate selected in this application includes at least one aliphatic ring as the hard segment monomer. The number of carbon atoms in the aliphatic ring is more than five. Furthermore, the end groups of the hard segment monomer include isocyanate groups and do not contain any other unsaturated groups other than isocyanate groups. This ensures that the polymer binder has sufficient rigidity and structural stability, which helps to prevent the electrolyte or other external factors from corroding the binder, thereby maintaining the interface integrity and electrochemical performance of the battery during long cycles.

[0046] In some embodiments, the hard segment monomer can be a monocyclic isocyanate (with 1 aliphatic ring, n1=6), such as 1,4-cyclohexane diisocyanate; it can also be a polycyclic isocyanate (with more than 1 aliphatic ring, n1≥5), such as isophorone diisocyanate, norbornene diisocyanate, etc.; or it can be a hydrogenated product containing a benzene ring structure (with more than 1 aliphatic ring, n1=6), such as dicyclohexylmethane diisocyanate.

[0047] It should be noted that the chemical structure of the hard segment monomer can be determined and resolved using thermogravimetric analysis-infrared spectroscopy. For example, the number of aliphatic rings in the polyisocyanate of the hard segment monomer can be 1, 2, 3, 4, 5, 6, or any value within the range of any two of the above values; the number of carbon atoms n1 in the aliphatic ring can be 5, 6, 7, 8, 9, 10, 11, or any value within the range of any two of the above values.

[0048] In one optional embodiment, the mass content (r%) of the soft segment monomer in the polymer raw material is 13% to 47%. This ensures that the polymer binder possesses appropriate flexibility, glass transition temperature, and mechanical strength, better adapting to the volume changes of the silicon-based material in the negative electrode during battery charging and discharging, and preventing binder breakage and detachment. Simultaneously, it helps improve the swelling properties of the binder, enhances the compatibility between the electrode sheet and the electrolyte, and reduces the swelling of the binder in the negative electrode by the electrolyte, thereby improving the battery's cycle performance and safety, and extending its cycle life.

[0049] This study found that when the mass content (r%) of soft segment monomers in the polymer raw materials is less than 13%, the binder's flexibility decreases, its glass transition temperature increases, and its rigidity increases. This leads to the binder being prone to breakage and detachment during battery operation. Furthermore, it cannot effectively adapt to the volume changes of silicon-based materials during battery charging and discharging. In addition, it also leads to poor wettability between the electrolyte and the negative electrode, thus affecting the battery's cycle performance. Conversely, when the mass content (r%) of soft segment monomers in the polymer raw materials is greater than 47%, the binder's affinity for the electrolyte intensifies, making it easier for the binder to penetrate the electrolyte. This increases the swelling of the binder by the electrolyte, which is detrimental to improving the battery's cycle life, capacity retention, and safety.

[0050] For example, the mass content of soft segment monomers is r%, which can be 13%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 47%, etc., or a value within the range of any two of the above values.

[0051] In one alternative implementation, the soft segment monomer satisfies at least one of the following conditions: A. The soft segment monomer has hydroxyl-terminated end groups; B. The number of carbon atoms n2 in the main chain of the soft segment monomer is 3 or more, preferably 5 or more; C. The main chain of the soft segment monomer does not contain any of the following: ether bonds, ester bonds, or carbon-carbon double bonds; D. The soft segment monomer includes a side chain, wherein the number of repeating units n3 of the side chain is less than 40, the number of carbon atoms in the side chain n4 is greater than or equal to 1, and the end group of the side chain includes at least one of methyl, cyano, and amide groups.

[0052] In this application, the soft segment monomer is end-capped with hydroxyl groups, and the main chain has three or more carbon atoms. Introducing hydroxyl-terminated long alkane blocks into the binder enables the formation of a more firmly bonded SEI film with lipophilic carbonates, reducing the swelling of the binder by the carbonates. Furthermore, the introduction of side chains with specific structures and compositions utilizes their steric hindrance effect to suppress the regular arrangement of molecular weights, reducing the crystallization tendency of the soft segment monomer during polymer binder preparation, thereby enhancing the flexibility of the polymer binder. Simultaneously, the side chain structure can also adjust the hydrophobicity and spatial configuration of the polymer binder, optimizing the compatibility between the polymer binder and the electrolyte, and preventing excessive swelling of the polymer binder by the electrolyte, thus improving the battery's cycle performance. In addition, excluding ether bonds, ester bonds, and carbon-carbon double bonds from the main chain of the soft segment monomer avoids the impact of ether bonds and ester bonds on battery cycle life, and avoids the impact of C=C unsaturated bonds on battery capacity performance.

[0053] It should be noted that the chemical structure of the soft segment monomer can be determined and resolved by thermogravimetric-pyrolysis gas chromatography-mass spectrometry. For example, the number of carbon atoms n2 in the main chain of the soft segment monomer can be 3, 5, 7, 11, 13, 15, 17, 19, 21, 23, 25, 27, 29, 31, 33, 35, or any value within the range of any two of the above values; the number of repeating units n3 in the side chain can be, for example, 40, 38, 36, 34, 32, 30, 28, 26, 24, 22, 20, or any value within the range of any two of the above values; the number of carbon atoms n4 in the side chain can be, for example, 1, 3, 5, 7, 9, 11, 13, 15, or any value within the range of any two of the above values.

[0054] In one optional embodiment, the soft segment monomer comprises at least one of 2-methyl-1,5-pentanediol, 2,2-dimethyl-1,3-propanediol, 1,2-hydroxystearic acid derivatives, hydrogenated polyisobutylene glycol, dihydroxy-terminated polyethylene, dihydroxy-terminated hydrogenated polybutadiene, poly(ethylene-CO-1,2-butene) glycol, dihydroxy-terminated polymers of (2-acrylonitrile, 1,3-butadiene), and 6-aminohexanoic acid derivatives.

[0055] In one alternative embodiment, the raw materials for the polymer further include a crosslinking agent, a hydrophilic chain extender, and a neutralizing agent.

[0056] In some embodiments, the crosslinking agent in the polymer raw material comprises at least three hydroxyl groups and has a molecular weight ≤200. The use of a crosslinking agent with at least three hydroxyl groups and a molecular weight ≤200 in the polymer raw material of this application is beneficial for constructing a polymer system with a three-dimensional network structure, thereby improving the adhesive effect of the polymer adhesive and allowing the polymer adhesive to simultaneously improve the electrolyte retention capacity and reduce the swelling effect of the electrolyte. If the number of hydroxyl groups in the crosslinking agent is less than three, a polymer system with a three-dimensional network structure cannot be effectively constructed. This affects the adhesive strength and adhesion durability of the polymer adhesive and also leads to poor compatibility between the adhesive and the electrolyte, resulting in a decrease in battery cycle performance. If the molecular weight of the crosslinking agent is greater than 200, it will lead to increased steric hindrance in the resulting polymer and incomplete crosslinking reaction, thereby affecting the construction of the three-dimensional network structure in the polymer adhesive, thus affecting the adhesive effect of the polymer adhesive and hindering the reduction of electrolyte swelling of the adhesive.

[0057] It should be noted that the chemical structure of the crosslinking agent can be determined and analyzed using thermogravimetric-pyrolysis gas chromatography-mass spectrometry. For example, the number of hydroxyl groups in the crosslinking agent is 3, 4, 5, 6, 7, 8, 9, 10, 11, or any value within the range of any two of the above values; the molecular weight of the crosslinking agent is 200, 180, 160, 140, 120, 100, 80, 60, 40, 20, or any value within the range of any two of the above values.

[0058] In some embodiments, the crosslinking agent specifically includes at least one of trimethylolpropane, glycerol, and pentaerythritol.

[0059] In some embodiments, the crosslinking agent content is 0.05% to 5.3% by mass, based on the total mass of the polymer raw materials. This ensures that the resulting polymer adhesive has an appropriate crosslinking density to form an effective three-dimensional network structure and maintain the elasticity of the adhesive, thereby improving the chemical and thermal stability of the adhesive and enabling the resulting polymer adhesive to better adapt to volume changes in silicon-based materials, thus improving the cycle performance and safety of the battery.

[0060] It should be noted that the mass content of the crosslinking agent can be obtained through thermogravimetric analysis. For example, the mass content of the crosslinking agent can be 0.05%, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.3%, or a value within any two of the above ranges.

[0061] In some embodiments, the hydrophilic chain extender in the raw materials of the polymer comprises at least two hydroxyl groups and at least one carboxyl group, with a molecular weight ≤204. The addition of the hydrophilic chain extender can introduce the hydrophilic carboxyl group, which can be converted into a carboxylate in the presence of a neutralizing agent. This improves the dispersibility and stability of the polymer binder during the preparation of the negative electrode slurry, ensures the uniformity of the raw materials in the negative electrode slurry, guarantees the binder's adhesive effect, and further enhances the mechanical strength and stability of the polymer binder, effectively preventing the electrolyte or other external factors from corroding the binder, thereby extending the battery's cycle life and improving its cycle performance and safety.

[0062] This study found that if the hydrophilic chain extender does not contain carboxyl groups and has fewer than two hydroxyl groups, it will affect the dispersibility and stability of the polymer binder during the preparation of the negative electrode slurry, and will not effectively ensure the uniformity of the raw materials in the negative electrode slurry, thus affecting the performance of the negative electrode sheet. Furthermore, it will also affect the construction of the polymer's three-dimensional network structure, weakening the bonding effect of the resulting polymer binder. This will prevent the binder from being effectively eroded by the electrolyte or other external factors, thereby affecting the battery's cycle performance and safety. If the molecular weight of the hydrophilic chain extender is higher than 204, the steric hindrance increases, and the reactivity decreases, leading to incomplete chain extension and uneven distribution of hydrophilic groups. This will affect the dispersibility and stability of the binder during the preparation of the negative electrode slurry, preventing the binder from fully exerting its bonding effect and adversely impacting the improvement of battery cycle performance and safety, and the extension of battery cycle life.

[0063] It should be noted that the chemical structure of the hydrophilic chain extender can be determined and analyzed by thermogravimetric-pyrolysis gas chromatography-mass spectrometry. The number of hydroxyl groups in the hydrophilic chain extender is 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or any value within the range of any two of the above values; the number of carboxyl groups in the hydrophilic chain extender is 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or any value within the range of any two of the above values; the molecular weight of the hydrophilic chain extender is 204, 200, 180, 160, 140, 120, 100, 80, 60, 40, 20, or any value within the range of any two of the above values.

[0064] In some embodiments, the hydrophilic chain extender includes at least one of 2,2-bis(hydroxymethyl)propionic acid, 2,2-dihydroxymethylbutyric acid, dihydroxymaleic acid, 2,6-dihydroxybenzoic acid, and 3,4-diaminobenzoic acid.

[0065] In some embodiments, the hydrophilic chain extender has a mass content of 1% to 8% based on the total mass of the polymer raw materials. This ensures the uniformity of raw material distribution in the negative electrode slurry, fully utilizes the adhesive effect of the binder, and improves the mechanical strength and stability of the polymer binder. It also effectively prevents the binder from being corroded by the electrolyte or other external factors, thereby further extending the cycle life of the battery and improving its cycle performance and safety.

[0066] For example, the mass content of the hydrophilic chain extender in the polymer raw material may be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, etc., or a value within the range of any two of the above values.

[0067] In some embodiments, the neutralizing agent comprises an inorganic base. Exemplarily, the inorganic base includes at least one selected from sodium hydroxide, potassium hydroxide, and sodium bicarbonate. This enables the conversion of hydrophilic carboxyl groups to carboxyl salts, thereby improving the dispersibility and stability of the polymer binder during the preparation of the negative electrode slurry, and enhancing the adhesive effect of the polymer binder.

[0068] In some embodiments, the neutralizing agent content is 0.5% to 5% based on the total mass of the polymer raw materials. For example, the mass content of the neutralizing agent in the polymer raw materials may be 0.5%, 1%, 2%, 3%, 4%, 5%, or a value within the range of any two of the above values.

[0069] In some embodiments, the polymer feedstock further includes catalyst molecules, including organotin and / or organobismuth molecules. The use of organotin and / or organobismuth catalysts can significantly reduce the activation energy of any component in the polymer feedstock, improve the polymerization efficiency of monomer molecules, and ensure high regularity and high degree of polymerization of the polymer molecular structure.

[0070] For example, the catalyst molecule includes at least one of dibutyltin dilaurate, stannous octanoate, dibutyltin diacetate, dibutyltin thiolate, bismuth isooctanoate, and bismuth neodecanoate.

[0071] In some embodiments, the mass content of the catalyst molecules is 0.01% to 1% based on the total mass of the polymer raw materials. For example, the mass content of the catalyst molecules may be 0.01%, 0.1%, 0.2%, 0.4%, 0.6%, 0.8%, 1%, or a value within any two of the above values.

[0072] In some embodiments, the polymer raw materials further include organic amine chain extenders, wherein the number of amine groups n5≥2. This enhances the structural rigidity and cohesive strength of the polymer, enabling the polymer adhesive to maintain excellent bonding performance and long-term cycle stability during battery charging and discharging. This is mainly because the amine groups in the organic amine chain extender can react with the isocyanate groups (-NCO) in the hard segment monomer to form urea bonds (-NH-CO-NH-).

[0073] For example, the organic amine chain extender may include at least one of ethylenediamine, isophorone diamine, diethyltoluene diamine, 3,5-diaminobenzoic acid, di-n-butylamine, diethylenetriamine, and triethylamine.

[0074] In some embodiments, the organic amine chain extender has a mass content of 1% to 5% based on the total mass of the raw materials of the polymer. For example, the mass content of the organic amine chain extender may be 1%, 2%, 3%, 4%, 5%, or a value within any two of the above values.

[0075] It should be noted that, in this application, "the total mass of the raw materials of the polymer" refers to the sum of the mass of the hard segment monomers, the soft segment monomers, the crosslinking agent, the hydrophilic chain extender, the neutralizing agent, the organic amine chain extender, and the catalyst molecules in the raw materials.

[0076] In some embodiments, the number-average molecular weight of the polymer is 10,000 to 100,000. This ensures that the polymer adhesive has a superior bonding effect and is more effective in preventing the adhesive from being corroded by electrolyte solvents or other external factors, thereby extending the battery's cycle life and improving its cycle performance and safety.

[0077] It should be noted that the method for determining the number-average molecular weight of polymers includes: mixing and reacting the raw materials for preparing the polymer (hard segment monomers, soft segment monomers, crosslinking agents, hydrophilic chain extenders, neutralizing agents, organic amine chain extenders, catalyst molecules) and solvents (water and methyl ethyl ketone) to obtain a polymer emulsion, and then drying it to obtain a gel film; taking a gel film sample, dissolving it in tetrahydrofuran, filtering it, and injecting it into a gel permeation chromatograph for molecular weight analysis, and calibrating it using a polystyrene standard sample. For example, the number average molecular weight of the polymer can be 10,000, 15,000, 20,000, 25,000, 30,000, 35,000, 40,000, 45,000, 50,000, 55,000, 60,000, 65,000, 70,000, 75,000, 80,000, 85,000, 90,000, 95,000, 100,000, or a value within the range of any two of the above values.

[0078] In one optional embodiment, the bonding surface diameter of the negative electrode adhesive is 10 nm to 1000 nm. This results in a relatively large surface roughness of the adhesive, which facilitates adhesive penetration, enhances the adhesion between the adhesive and the negative electrode active material, and makes the adhesive less prone to detachment or deformation when eroded by substances in the electrolyte, thereby mitigating the swelling phenomenon of the adhesive and enhancing its stability.

[0079] This study found that when the bonding surface diameter of the negative electrode binder is less than 10 nm, the binder is excessively dispersed and cannot form an effective network structure. The binder's adhesion is insufficient and it cannot effectively adapt to the volume changes of silicon-based materials during battery charging and discharging, thus affecting the battery's cycle performance. Conversely, when the bonding surface diameter of the negative electrode binder is greater than 1000 nm, the binder agglomerates severely, increasing the continuous channels and promoting the penetration of electrolyte into the binder, which easily leads to swelling. Furthermore, an excessively high bonding surface diameter results in incomplete contact between the binder and the negative electrode active material, making the negative electrode structure unstable and thus affecting the battery's cycle performance and safety.

[0080] For example, the bonding surface diameter of the negative electrode adhesive is 10 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, or a value within the range of any two of the above values.

[0081] In one optional embodiment, the mass content (t%) of the carbonate substances is 10% to 40% based on the total mass of the electrolyte. This promotes the formation of a relatively stable SEI film on the surface of the silicon-based negative electrode, stabilizing the electrode structure during battery charging and discharging, ensuring the battery's electrochemical performance. Simultaneously, it reduces the content of free carbonate substances in the electrolyte, thereby reducing the swelling of the binder and improving the battery's cycle life, capacity retention, and safety.

[0082] This study found that when the mass content (t%) of carbonates in the electrolyte is less than 10%, the formation of a complete and relatively dense SEI film cannot be guaranteed, which is not conducive to preventing the subsequent penetration of the electrolyte into the negative electrode and easily leads to the occurrence of side reactions, thereby deteriorating the electrochemical performance of the battery. Conversely, when the mass content (t%) of carbonates in the electrolyte is greater than 40%, free carbonates, in addition to promoting film formation, will penetrate into the binder, reducing the interaction force between polymer binders and causing the binder material to swell, which is not conducive to improving the cycle life, capacity retention and safety of the battery.

[0083] For example, the mass content t% of carbonate substances can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, or a value within the range of any two of the above values.

[0084] In one optional embodiment, the carbonate substances in the electrolyte include at least two of ethylene carbonate, propylene carbonate, diethyl carbonate, methyl ethyl carbonate, dimethyl carbonate, and fluoroethylene carbonate.

[0085] In one optional embodiment, when the carbonate material in the electrolyte includes ethylene carbonate, the mass content of ethylene carbonate is less than 10% based on the total mass of the electrolyte. Ethylene carbonate, as a typical carbonate material, has a strong dipole moment, making it more likely to interact with polar groups in the binder, penetrating into the binder and reducing the interaction forces between polymer chains. This significantly affects the swelling of the binder. By further controlling the mass content of ethylene carbonate, a stable SEI film formation can be ensured while reducing the swelling of the negative electrode binder by the electrolyte. If the mass content of ethylene carbonate is higher than 10%, the electrolyte will easily cause swelling of the negative electrode binder, thus affecting the cycle performance and safety of the battery.

[0086] In one optional embodiment, the electrolyte further includes carboxylic acid esters. Carboxylic acid esters have lower intermolecular forces, which can reduce the viscosity of the electrolyte and reduce the resistance to lithium ion movement in the electrolyte. Furthermore, carboxylic acid esters have a lower swelling effect on the adhesive compared to carbonates. Replacing some of the carbonates in the electrolyte with carboxylic acid esters can improve the kinetic performance of the electrolyte and reduce the swelling of the adhesive by the electrolyte. However, this application found that carboxylic acid esters, as polar solvents, contain polar ester groups (-COOR) in their molecules. When they come into contact with the polymer materials in the polymer binder, a certain polar interaction still occurs between them. This leads to the rearrangement or relaxation of the molecular chains of the materials, weakening the interaction between polymer chains and causing the membrane material to swell. Furthermore, due to the small size and strong solubility of carboxylic acid ester molecules, they can easily diffuse into the polymer. When the solvent enters the pores and voids of the polymer, the carboxylic acid esters cause the negative electrode structure to expand. This is mainly because the solvent molecules fill the gaps between polymer chains, reducing the degree of cross-linking between polymer chains and making the negative electrode material loose. Therefore, this application further requires controlling the mass content of low-viscosity carboxylic acid esters to 37%~70% to further reduce the swelling phenomenon of the binder by the electrolyte while ensuring the excellent dynamic performance of the battery, thereby more effectively improving the cycle performance and safety of the battery and extending the cycle life of the battery.

[0087] This study found that when the mass content of carboxylic acid esters in the electrolyte is less than 37%, the viscosity of the electrolyte increases, the resistance to the movement of lithium ions in the electrolyte increases, and the kinetic performance of the electrolyte decreases, resulting in poorer electrochemical performance of the battery. Conversely, when the mass content of carboxylic acid esters in the electrolyte is greater than 70%, the electrolyte diffuses more easily and the polymer binder swells significantly, which is detrimental to improving the cycle performance and safety of the battery.

[0088] It should be noted that the mass content of carboxylic acid esters in the electrolyte can be obtained by gas chromatography. For example, the mass content of additives in the electrolyte can be 37%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, or a value within any two of the above ranges.

[0089] In one optional embodiment, the carboxylic acid ester includes at least one of propyl propionate, ethyl propionate, ethyl butyrate, propyl acetate, ethyl acetate, and difluoroethyl acetate.

[0090] In one optional embodiment, the electrolyte further includes additives. This promotes the formation of a stable and dense SEI film, ensuring battery cycle performance while mitigating the swelling of the negative electrode binder by the electrolyte, thereby improving battery cycle life, capacity retention, and safety.

[0091] In an optional embodiment, the additive comprises at least one selected from 1,3-propanesulfonyl lactone, lithium difluorophosphate, vinylene carbonate, ethylene ethylene carbonate, vinyl sulfate, 4-methyl-ethylene sulfate, triargyl propargyl phosphate, 1,3,5-pentanetricarbonyl, 1,2,3-propanetricarbonyl, 1,3,6-hexanetricarbonyl, 1,2,6-hexanetricarbonyl, ethylene glycol di(2-cyanoethyl) ether, diethylene glycol di(2-cyanoethyl) ether, triethylene glycol di(2-cyanoethyl) ether, 1,2,3,4,5-penta(2-cyanoethoxy)pentane, tetraethylene glycol di(2-cyanoethyl) ether, ethylene glycol di(4-cyanobutyl) ether, ethylene glycol (bis)propionitrile ether, and tri(3-cyanopropyl) phosphate.

[0092] In one optional embodiment, the additive content is 2.7% to 10.9% by mass, based on the total mass of the electrolyte. This improves film formation, resulting in a uniform and relatively dense SEI film that effectively blocks the erosion of the binder by the electrolyte or other external factors, thereby maintaining a long battery life. Simultaneously, the addition of a specific amount of additive can effectively inhibit electrolyte penetration into the negative electrode, reducing the swelling effect of the electrolyte on the negative electrode binder, which is beneficial for improving the battery's cycle performance and safety performance.

[0093] It should be noted that the mass content of additives in the electrolyte can be obtained by gas chromatography. For example, the mass content of additives in the electrolyte can be 2.7%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, 10.9%, or a value within any two of the above ranges.

[0094] In one optional embodiment, the lithium salt content is 11.4% to 24.8% based on the total mass of the electrolyte. As a cornerstone of the electrolyte, the lithium salt provides lithium ions, improves the ionic conductivity of the electrolyte, provides sufficient lithium source for the formation of a stable SEI film, ensures suitable viscosity of the electrolyte, and reduces side reactions at the negative electrode interface, thereby ensuring excellent electrochemical performance of the battery. Furthermore, the addition of an appropriate amount of lithium salt can avoid the salting-out effect caused by high-concentration lithium salts, thus reducing the swelling of the binder. Therefore, controlling the appropriate lithium salt content can ensure excellent electrochemical cycle performance of the battery while also promoting the reduction of electrolyte swelling of the polymer binder.

[0095] It should be noted that the mass content of lithium salt in the electrolyte can be obtained by ion chromatography. For example, the mass content of lithium salt in the electrolyte may be 11.4%, 12.0%, 14.0%, 16.0%, 18.0%, 20.0%, 22.0%, 24.0%, 24.8%, or a value within any two of the above ranges.

[0096] In one optional embodiment, the lithium salt includes at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorooxalate borate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorobis(oxalate phosphate), lithium tetrafluoroborate, lithium bis(oxalate borate), lithium hexafluoroantimonyate, lithium hexafluoroarsenate, lithium di(pentafluoroethylsulfonyl)imide, and lithium tri(trifluoromethanesulfonyl)methyl, preferably lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide. This application research has found that lithium salts have different solubilities and ionic conductivity in electrolytes. Compared to single ordinary lithium salts, mixed lithium salts exhibit better high-temperature storage performance, can adjust the ionic conductivity of the electrolyte, and maintain good conductivity under various temperatures and operating conditions. Good electrolyte conductivity effectively reduces battery internal resistance and avoids overheating problems caused by excessive internal resistance. The lithium hexafluorophosphate (LiPF6) in the lithium salt contains PF6. - The ions possess moderate ionic radii and charge densities, providing sufficiently high ionic conductivity over a wide operating temperature range, and promoting SEI film formation. This effectively blocks the influence of electrolytes or other factors on the binder. The FSI in lithium bis(fluorosulfonyl)imide (LiFSI) - Ions have better chemical stability and are not easily decomposed into more corrosive substances even under high temperature conditions. LiPF6 and LiFSI in lithium salts work together to improve the thermal stability of the battery.

[0097] In one optional embodiment, based on the total mass of the electrolyte, the lithium hexafluorophosphate content is 10.7%~16.2% and the lithium bis(fluorosulfonyl)imide content is 2.9%~8.7%. This ensures sufficiently high ionic conductivity over a wide operating temperature range, promotes SEI film formation, guarantees the electrochemical stability of the electrolyte, improves battery thermal stability and cycle performance, and extends battery cycle life.

[0098] It should be noted that the mass content of lithium hexafluorophosphate and lithium difluorosulfonylimide in the electrolyte can be obtained by ion chromatography. For example, the mass content of lithium hexafluorophosphate in the electrolyte can be, for example, 10.7%, 11.0%, 12.0%, 13.0%, 14.0%, 15.0%, 16.0%, 16.2%, or values ​​within any two of the above ranges; the mass content of lithium difluorosulfonylimide in the electrolyte can be, for example, 2.9%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, 8.0%, 8.7%, or values ​​within any two of the above ranges.

[0099] In one optional embodiment, the silicon-based material in the negative electrode active material includes silicon, and the mass content of silicon is 35% to 70% based on the total mass of the silicon-based material. This ensures excellent electrochemical performance of the battery, while the silicon-based material with a specific silicon content can work synergistically with the binder, allowing the binder to better adapt to the volume changes of the silicon-based material during charge and discharge, improving the structural stability of the negative electrode, and thus improving the cycle life and safety of the battery. If the mass content of silicon is higher than 70%, the binder, while maintaining low swelling, cannot effectively adapt to the volume changes of the silicon-based material during charge and discharge, resulting in poor structural stability of the negative electrode and affecting the cycle performance and safety performance of the battery. If the mass content of silicon is lower than 35%, the battery's capacity performance will deteriorate, and the battery will not be able to achieve high capacity performance.

[0100] It should be noted that the mass content of silicon in silicon-based materials can be obtained by scanning electron microscopy (SEM) energy dispersive spectroscopy. For example, the mass content of silicon in silicon-based materials can be 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, or values ​​within any two of the above ranges.

[0101] In some embodiments, the silicon-based material includes at least one of silicon-oxygen materials, silicon-carbon materials, and silicon-oxygen-carbon materials.

[0102] In one optional embodiment, the particle size D50 of the silicon-based material is 3 μm to 15 μm. This ensures uniform silicon particle size, guaranteeing sufficient adhesion of the adhesive to the silicon-based material and better adapting to volume changes in the silicon-based material, while also allowing the adhesive to fully utilize its flexibility, thereby enabling the negative electrode to better adapt to physical changes caused by thermal expansion and contraction.

[0103] It should be noted that the particle size D50 of silicon-based materials can be obtained by measuring a Malvern laser particle size analyzer. For example, the particle size D50 of silicon-based materials can be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, etc., or values ​​within any two of the above ranges.

[0104] In one optional embodiment, the specific surface area of ​​the silicon-based material is 0.5 m². 2 / g~3 m 2 / g. In this way, sufficient active sites can be provided for the reaction to ensure the electrochemical performance of the battery. At the same time, the amount of binder can be reduced, as well as the contact area between the binder and the electrolyte can be reduced, thus reducing the swelling of the binder by the electrolyte, thereby improving the cycle performance and safety of the battery and extending the cycle life of the battery.

[0105] It should be noted that the specific surface area of ​​silicon-based materials can be obtained by testing using the BET nitrogen adsorption method. For example, the specific surface area of ​​a silicon-based material could be, for instance, 0.5 m². 2 / g, 1.0 m 2 / g, 1.5 m 2 / g, 2.0 m 2 / g, 2.5 m 2 / g, 3.0m 2 / g or values ​​within the range of any two of the above values.

[0106] In this application, the content ratio between the negative electrode active layer and the electrolyte is not specifically limited. For example, in some embodiments, the ratio of the total mass of the negative electrode active layer to the total mass of the electrolyte can be 1:(0.3~2). For example, the ratio of the total mass of the negative electrode active layer to the total mass of the electrolyte can be, for example, 1:0.3, 1:0.4, 1:0.6, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, etc., or a value within the range of any two of the above values.

[0107] In this application, the mass content of the polymer binder in the negative electrode active layer is not specifically limited. Exemplarily, in some embodiments, based on the total mass of the negative electrode active layer, the mass content of the polymer binder is 0.2% to 10%. Exemplarily, the mass content of the polymer binder in the negative electrode active layer can be, for example, 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc., or a value within the range formed by any two of the above values.

[0108] In an optional embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer provided on at least one surface of the positive electrode current collector, and the positive electrode active layer includes a positive electrode active material.

[0109] In an optional embodiment, the positive electrode active material includes a positive electrode active material, or includes a positive electrode active material and a coating layer provided on the surface of the positive electrode active material.

[0110] In an optional embodiment, the positive electrode active material includes LiNi x Co y Mn z M a O2, where 0.8 ≤ x ≤ 0.95, 0.01 ≤ y ≤ 0.18, 0.01 ≤ z ≤ 0.18, 0 < a ≤ 0.1, and M includes at least one of Al, Mg, Y, W, B, Zr, Ti, Sr, La, Nb. Exemplarily, x in the positive electrode active material can be, for example, 0.8, 0.82, 0.84, 0.86, 0.88, 0.90, 0.92, 0.94, 0.95, etc., or a value within the range formed by any two of the above values; y in the positive electrode active material can be, for example, 0.01, 0.02, 0.04, 0.06, 0.08, 0.10, 0.12, 0.14, 0.16, 0.18, etc., or a value within the range formed by any two of the above values; z in the positive electrode active material can be, for example, 0.01, 0.02, 0.04, 0.06, 0.08, 0.10, 0.12, 0.14, 0.16, 0.18, etc., or a value within the range formed by any two of the above values; a in the positive electrode active material can be, for example, 0.01, 0.02, 0.04, 0.06, 0.08, 0.10, etc., or a value within the range formed by any two of the above values.

[0111] In an optional embodiment, the coating layer includes a metal oxide. Exemplarily, the metal oxide can be, for example, at least one of aluminum oxide (Al2O3), zirconium oxide (ZrO2), titanium oxide (TiO2), magnesium oxide (MgO), zinc oxide (ZnO).

[0112] In one optional embodiment, the thickness of the coating layer is 10 nm to 50 nm. It should be noted that the thickness of the coating layer in the positive electrode active material can be obtained by transmission electron microscopy (TEM). For example, the thickness of the coating layer can be 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, or a value within any two of the above ranges.

[0113] In one alternative embodiment, the positive electrode active material comprises monocrystalline particles and / or polycrystalline particles.

[0114] In one optional embodiment, the particle size D50 of the positive electrode active material is 1 μm to 15 μm. For example, the particle size D50 of the positive electrode active material can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, or a value within any two of the above values.

[0115] In the following examples, 1,4-cyclohexane diisocyanate was commercially available, CAS number: 2556-36-7; 2-methyl-1,5-pentanediol was commercially available, CAS number: 42856-62-2; trimethylolpropane was commercially available, CAS number: 77-99-6; 2,2-bis(hydroxymethyl)propionic acid was commercially available, CAS number: 4767-03-7; and ethylenediamine was commercially available, CAS number: 107-15. -3; Dibutyltin dilaurate is commercially available, CAS No.: 77-58-7; Dihydroxy-terminated hydrogenated polybutadiene is commercially available, CAS No.: 69102-90-5; Hydroxyl-terminated polyethylene is commercially available, CAS No.: 68987-46-2; Hexamethylene diisocyanate is commercially available, CAS No.: 822-06-0; Toluene-2,4-diisocyanate is commercially available, CAS No.: 584-84-9 Diphenylmethane diisocyanate is commercially available, CAS number: 101-68-8; trihydroxy polyoxypropylene ether is commercially available, CAS number: 25791-96-2; 1,4-butanediol is commercially available, CAS number: 110-63-4; isophorone diisocyanate is commercially available, CAS number: 4098-71-9; norbornene diisocyanate is commercially available, CAS number: 279-23-2; dicyclohexylmethyl... Alkane diisocyanate is commercially available, CAS number: 5124-30-1; 2,2-dimethyl-1,3-propanediol is commercially available, CAS number: 126-30-7; hydrogenated polyisobutylene glycol is commercially available, CAS number: 68937-10-0; 2,2-dimethylolbutyric acid is commercially available, CAS number: 10097-02-6; 2,6-dihydroxybenzoic acid is commercially available, CAS number: 303-07-1.

[0116] Example 1 This embodiment provides a method for preparing a secondary battery, including the following steps: (1) Preparation of polymer adhesive precursor-polymer emulsion To a reactor equipped with stable monitoring and stirring equipment, add sequentially the following components by weight: 339 parts by weight of 1,4-cyclohexane diisocyanate (hard segment monomer), 105 parts by weight of 2-methyl-1,5-pentanediol (soft segment monomer), 12.5 parts by weight of trimethylolpropane (crosslinking agent), and 20 parts by weight of 2,2-bis(hydroxymethyl)propionic acid (hydrophilic chain extender). Then, purge the reactor with nitrogen gas, maintain the reaction temperature at 70-75°C, and allow the reaction time to 4 hours. The content of isocyanate (-NCO) groups in the reactor is determined using the di-n-butylamine titration method until no is detected. To remove free NCO residue, 100-300 parts of methyl ethyl ketone (MEK) were used as a solvent to adjust the viscosity. The temperature was lowered to 45°C, and 11 parts of sodium hydroxide (neutralizing agent) were added for neutralization. 1900 parts of water were slowly added to the reactor, and emulsification and dispersion were carried out using an emulsifier. 10 parts of ethylenediamine (organic amine chain extender) and 2.5 parts of dibutyltin dilaurate (catalyst molecule) were added to 100 parts of water, and this aqueous solution was added to the reactor for chain extension. After the reaction was completed, MEK was removed under reduced pressure to obtain a polymer emulsion with a solid content of 20%.

[0117] (2) Preparation of electrolyte In a glove box (H2O < 0.01 ppm, O2 < 0.01 ppm, Ar atmosphere), 7% ethylene carbonate (EC) and 64% carboxylic acid esters (PP and EP) by mass ratio of the total electrolyte were uniformly mixed. The carboxylic acid esters were propyl propionate (PP) and ethyl propionate (EP) in a mass ratio of 49:15. 12.5% ​​fully dried lithium hexafluorophosphate (LiPF6) and 4% lithium bis(fluorosulfonyl)imide (LiFSI) by mass of the total electrolyte were added. Then, 8% fluoroethylene carbonate (FEC) and additives (including 3% 1,3-propanesulfonyl lactone (PS), 0.5 wt% lithium difluorophosphate (LiPO2F2), and 1% ethylene sulfate (DTD) by mass of the total electrolyte) were added and stirred until homogeneous. After passing the moisture and free acid tests, the electrolyte was obtained.

[0118] (3) Preparation of negative electrode sheet Artificial graphite, silicon-based materials, conductive carbon black, the solids in the polymer emulsion prepared in step (1), and sodium carboxymethyl cellulose were mixed evenly in a mass ratio of 82.3:15:1.7:0.5:0.5. Deionized water was added, and the mixture was stirred thoroughly to form a uniform negative electrode slurry. The negative electrode slurry was coated on both sides of the copper foil surface, dried, rolled, cut, and cleaned to obtain a negative electrode sheet. The obtained negative electrode sheet includes a current collector and a negative electrode active layer disposed on the surface of the current collector. The negative electrode active layer includes a negative electrode active material (artificial graphite), silicon-based materials, conductive carbon black, polymer binder, and sodium carboxymethyl cellulose. The added silicon-based material is silicon-carbon material, with a silicon element mass content of 46%, a particle size D50 of 10 μm, and a specific surface area of ​​1.2 m². 2 / g.

[0119] (4) Preparation of positive electrode sheet The positive electrode active material, conductive agent (a mixture of conductive carbon black and carbon nanotubes at a mass ratio of 2:1), and PVDF at a mass ratio of 97.60:1.5:0.9 were placed in NMP and stirred evenly to obtain a positive electrode slurry. This slurry was then uniformly coated onto both sides of an aluminum foil. The foil was subsequently dried and rolled to obtain a positive electrode sheet. The positive electrode active material included LiNi. 0.8 Co 0.06 Mn 0.08 Y 0.06 O2, the positive electrode active material is a single crystal particle, and the particle size D50 of the positive electrode active material is 4 μm.

[0120] (5) Battery fabrication The negative electrode sheet prepared in step (3), the positive electrode sheet prepared in step (4), and the separator (a 5 μm thick polypropylene substrate, a 1 μm thick ceramic layer on one side of the substrate, and a 1 μm thick polyvinylidene fluoride adhesive layer on the other side of the substrate and on the side of the ceramic layer away from the substrate) are wound into a core according to a predetermined process. The electrolyte prepared in step (2) is injected. The ratio of the total mass of the added electrolyte to the total mass of the negative electrode active layer is 1:1. After vacuum sealing, standing, formation, sorting, and secondary sealing, a secondary battery is prepared.

[0121] The preparation methods of Examples 2-29 and Comparative Examples 1-5 are basically the same as those of Example 1. The differences are shown in Tables 1, 2, and 3. " / " indicates that the item does not exist. In Tables 1-3, the mass content r% of the soft segment monomer refers to the percentage of the total mass fraction of soft segment monomers, hard segment monomers, crosslinking agents, hydrophilic chain extenders, neutralizing agents, organic amine chain extenders, and catalyst molecules added during the preparation of the polymer adhesive, denoted as A parts. Similarly, the mass content of the hard segment monomer refers to the percentage of the mass fraction of the hard segment monomer relative to A parts. The mass content (t%) of carbonates refers to the mass percentage of carbonates in the electrolyte; the mass content (%) of EC refers to the mass percentage of EC in the electrolyte; the mass content (%) of FEC refers to the mass percentage of FEC in the electrolyte; the mass content (%) of carboxylic acid esters refers to the mass percentage of carboxylic acid esters in the electrolyte; and the mass contents of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide are the mass percentages of lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide in the electrolyte, respectively. In Examples 28 and 29, the coating type and coating thickness refer to the type and thickness of the coating on the surface of the positive electrode active material.

[0122] Table 1

[0123]

[0124] Table 2

[0125] Table 3

[0126] 1. Electrolyte swelling effect test on adhesive According to the national standard GB / T 1725-2007 Determination of solid content of polyurethane emulsion, the adhesive precursor-polymer emulsion prepared in step (1) of the above examples and comparative examples was poured into a polytetrafluoroethylene mold and left to stand at room temperature, horizontal and dust-free environment until surface dry. Then the sample was transferred to a 50°C constant temperature oven for continuous drying until the film quality was constant. Finally, a polymer film with a smooth surface and no bubbles was obtained. After demolding, it was placed in a desiccator for storage. The swelling rate of the adhesive film in the electrolyte prepared in step (2) is tested. The specific test method includes: immersing the well-formed adhesive film (thickness 100 μm-200 μm) with an initial mass of m1 completely into the electrolyte prepared in step (2), letting it stand at a constant temperature of 60℃ for 72 hours, taking it out, gently blotting the residual electrolyte on the surface with filter paper, and weighing the mass after swelling as m2; the formula for calculating the mass swelling rate is: swelling rate (%) = (m2-m1) / m1×100%.

[0127] 2. Cyclic performance test A. Cyclic performance test at room temperature: The cycle performance of the secondary batteries provided in the above embodiments and comparative examples was tested at 25℃±2℃.

[0128] 1) Let stand at 25℃±2℃ for 10 min; 2) Discharge at 0.2C to the lower limit voltage of 3V, let stand for 10 min; 3) Charge at 0.7C to the upper limit voltage of 4.25V, cut off at 0.025C, let stand for 10 min; 4) Discharge at 0.2C to the lower limit voltage of 3V, the initial discharge capacity is recorded as C1; 5) Let stand for 10 min; 6) Charge at 2C to 4.25V (cut off at 1.5C), then charge at 1.5C to 4.3V (cut off at 1.5C). C) Next, charge at 1C to 4.5V (cutoff at 0.25C), and test the first full-charge data: voltage, internal resistance, thickness, and DC internal resistance; 7) Let stand at 25℃±2℃ for 10 minutes; 8) Discharge at 0.7C to the lower limit voltage of 3V; let stand for 10 minutes; 9) Charge at 2C to 4.25V (cutoff at 1.5C), then charge at 1.5C to 4.3V (cutoff at 1C), then charge at 1C to 4.5V (cutoff at 0.25C), and let stand for 10 minutes; repeat steps 8) to 9) 600 times, record the discharge capacity, and denot it as C2. Calculate the capacity retention rate after 600 cycles = C2 / C1 × 100%.

[0129] B. Cyclic performance test at 45°C: The cycle performance of the secondary batteries provided in the above embodiments and comparative examples was tested at 45°C ± 2°C.

[0130] ① Let stand at 45℃±2℃ for 10 minutes; ② Discharge at 0.2C to the lower limit voltage of 3V, let stand for 10 minutes; ③ Charge at 0.7C to the upper limit voltage of 4.25V, cut off at 0.025C, let stand for 10 minutes; ④ Discharge at 0.2C to the lower limit voltage of 3V, the initial discharge capacity is recorded as C3; ⑤ Let stand for 10 minutes; ⑥ Charge at 2C to 4.25V (cut off at 1.5C), then charge at 1.5C to 4.3V (cut off at 1.5C). C), then charge at 1C to 4.5V (cutoff at 0.25C), and test the first full-charge data: voltage, internal resistance, thickness, and DC internal resistance; ⑦ Let stand at 45℃±2℃ for 10 minutes; ⑧ Discharge at 0.7C to the lower limit voltage of 3V; let stand for 10 minutes; ⑨ Charge at 2C to 4.25V (cutoff at 1.5C), then charge at 1.5C to 4.3V (cutoff at 1C), then charge at 1C to 4.5V (cutoff at 0.25C), and let stand for 10 minutes; repeat steps ⑧ to ⑨ 400 times, record the discharge capacity, and denot it as C4. Calculate the capacity retention rate after 400 cycles = C4 / C3 × 100%.

[0131] 3. Lithium plating test: The batteries obtained in the examples and comparative examples were charged in an environment of 25°C with the following time control: charging time from 10% to 80% SOC was 11 minutes (SOC is the battery's state of charge; a fully charged battery is 100% SOC, and an empty battery is 0% SOC); charging time from 0% to 10% SOC was 5 minutes; charging time from 80% to 100% SOC was 20 minutes; and discharging time was 60 minutes. This charge-discharge cycle was used to test the batteries. One charge and one discharge cycle was defined as one cycle. After fully charging, the batteries were allowed to rest for 30 minutes before being discharged again. This fast-charging cycle was used to test the batteries until 50 charge-discharge cycles were completed. On the 51st cycle, the batteries were fully charged using the fast-charging method (100% SOC). The batteries were then removed and disassembled to observe the lithium deposition on the surface of the negative electrode. The criteria for judging the lithium deposition phenomenon on the negative electrode were: 1) no lithium deposition; 2) lithium deposition on the top and bottom was considered slight lithium deposition; 3) lithium deposition across the entire surface was considered severe lithium deposition.

[0132] The test results are shown in Table 4.

[0133] Table 4

[0134] As can be seen from Tables 1-4, the secondary batteries prepared in Examples 1-29 maintain excellent long-cycle performance while exhibiting low swelling effect, thus demonstrating superior safety performance. This indicates that the secondary batteries provided in this application, through the optimization of the chemical structure in the binder and the adjustment of the composition in the electrolyte solution, work synergistically to ensure excellent electrochemical cycle performance while reducing the swelling effect of the electrolyte on the binder, thereby extending the battery's cycle life and improving its capacity retention and safety.

[0135] Compared to Example 1, the ratio of the mass content t% of carbonate substances in the electrolyte to the mass content r% of soft-segment monomers in the polymer raw material in the negative electrode of the secondary batteries provided in Comparative Examples 1-5 is outside the range of 0.234 to 1.770. This leads to an increase in the swelling rate of the binder, a decrease in the cycle performance of the battery, a decrease in thermal stability, and severe lithium plating. This indicates that when the ratio of the mass content t% of carbonate substances in the electrolyte to the mass content r% of soft-segment monomers in the polymer raw material fails to meet the requirements of a specific range, it leads to an increase in the swelling effect of the binder by the electrolyte, and a decrease in the structural stability and thermal stability of the negative electrode, thereby resulting in a deterioration in both the cycle performance and safety performance of the battery.

[0136] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A secondary battery, comprising a negative electrode, a positive electrode, a separator, and an electrolyte, wherein the negative electrode comprises a negative current collector and a negative active layer disposed on at least one surface of the negative current collector, the negative active layer comprising a negative active material and a negative binder, characterized in that, The negative electrode active material includes silicon-based materials; The negative electrode adhesive comprises a polymer, and the raw materials of the polymer include hard segment monomers and soft segment monomers; The electrolyte comprises carbonates and lithium salts; Based on the total mass of the raw materials for the polymer, the mass content of the soft segment monomer is r%; Based on the total mass of the electrolyte, the mass content of the carbonate substances is t%; Both satisfy the condition 0.234≤t / r≤1.

770.

2. The secondary battery according to claim 1, characterized in that, Based on the total mass of the raw materials of the polymer, the mass content of the hard segment monomer is s%, where s is 39.8~77.8%; And / or, the hard segment monomer satisfies at least one of the following conditions: a. The hard segment monomer comprises a polyisocyanate, the polyisocyanate comprising at least one aliphatic ring, wherein the number of carbon atoms in the aliphatic ring n1 ≥ 5; b. The two end groups of the hard segment monomer include isocyanate groups, and the hard segment monomer does not contain any other unsaturated groups other than isocyanate groups.

3. The secondary battery according to claim 1, characterized in that, The value of r is 13~47; And / or, the soft segment monomer satisfies at least one of the following conditions: A. The soft segment monomer has hydroxyl-terminated end groups; B. The number of carbon atoms n2 in the main chain of the soft segment monomer is 3 or more, preferably 5 or more; C. The main chain of the soft segment monomer does not contain any of the following: ether bonds, ester bonds, or carbon-carbon double bonds; D. The soft segment monomer includes a side chain, wherein the number of repeating units n3 of the side chain is less than 40, the number of carbon atoms in the side chain n4 is greater than or equal to 1, and the end group of the side chain includes at least one of methyl, cyano, and amide groups.

4. The secondary battery according to any one of claims 1 to 3, characterized in that, The hard segment monomer includes at least one of 1,4-cyclohexane diisocyanate, isophorone diisocyanate, norbornane diisocyanate, and dicyclohexylmethane diisocyanate. And / or, the soft segment monomer comprises at least one of 2-methyl-1,5-pentanediol, 2,2-dimethyl-1,3-propanediol, 1,2-hydroxystearic acid derivatives, hydrogenated polyisobutylene glycol, dihydroxy-terminated polyethylene, dihydroxy-terminated hydrogenated polybutadiene, poly(ethylene-CO-1,2-butene) glycol, dihydroxy-terminated polymers of (2-acrylonitrile, 1,3-butadiene), and 6-aminohexanoic acid derivatives; And / or, the raw materials of the polymer further include a crosslinking agent, a hydrophilic chain extender, and a neutralizing agent; the crosslinking agent comprises at least three hydroxyl groups and has a molecular weight ≤200; the hydrophilic chain extender comprises at least two hydroxyl groups and at least one carboxyl group and has a molecular weight ≤204.

5. The secondary battery according to claim 1, characterized in that, The bonding surface diameter of the negative electrode adhesive is 10 nm to 1000 nm.

6. The secondary battery according to any one of claims 1 to 3, characterized in that, The electrolyte satisfies at least one of the following conditions: I. The value of t is 10~40; II. The carbonate substances include at least two of the following: ethylene carbonate, propylene carbonate, diethyl carbonate, methyl ethyl carbonate, dimethyl carbonate, and fluoroethylene carbonate; III. The carbonate substance includes ethylene carbonate, and the mass content of ethylene carbonate is less than 10% based on the total mass of the electrolyte; IV. The electrolyte also includes carboxylic acid esters; V. The electrolyte also includes additives; VI. Based on the total mass of the electrolyte, the mass content of the lithium salt is 11.4% to 24.8%; VII. The lithium salt comprises at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium difluorooxalate borate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorobis(oxalate) phosphate, lithium tetrafluoroborate, lithium bis(oxalate) borate, lithium hexafluoroantimonyate, lithium hexafluoroarsenate, lithium di(pentafluoroethylsulfonyl)imide, and lithium tri(trifluoromethylsulfonyl)methyl, preferably lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide.

7. The secondary battery according to claim 6, characterized in that, Based on the total mass of the electrolyte, the mass content of the carboxylic acid esters is 37% to 70%. And / or, the carboxylic acid esters include at least one of propyl propionate, ethyl propionate, ethyl butyrate, propyl acetate, ethyl acetate, and difluoroethyl acetate; And / or, based on the total mass of the electrolyte, the mass content of the additive is 2.7% to 10.9%; And / or, the additive comprises at least one of 1,3-propanesulfonyl lactone, lithium difluorophosphate, vinylene carbonate, ethylene ethylene carbonate, vinyl sulfate, 4-methyl-vinyl sulfate, triargyl propargyl phosphate, 1,3,5-pentanetricarbonyl, 1,2,3-propanetricarbonyl, 1,3,6-hexanetricarbonyl, 1,2,6-hexanetricarbonyl, ethylene glycol di(2-cyanoethyl) ether, diethylene glycol di(2-cyanoethyl) ether, triethylene glycol di(2-cyanoethyl) ether, 1,2,3,4,5-penta(2-cyanoethoxy)pentane, tetraethylene glycol di(2-cyanoethyl) ether, ethylene glycol di(4-cyanobutyl) ether, ethylene glycol (bis)propionitrile ether, and tri(3-cyanopropyl) phosphate; And / or, based on the total mass of the electrolyte, the lithium hexafluorophosphate has a mass content of 10.7% to 16.2% and the lithium difluorosulfonylimide has a mass content of 2.9% to 8.7%.

8. The secondary battery according to claim 1, characterized in that, In the negative electrode active material, the silicon-based material includes silicon element, and the mass content of silicon element is 35% to 70% based on the total mass of the silicon-based material; And / or, the particle size D50 of the silicon-based material is 3 μm to 15 μm; And / or, the specific surface area of ​​the silicon-based material is 0.5 m². 2 / g~3 m 2 / g.

9. The secondary battery according to claim 1, characterized in that, The positive electrode sheet includes a positive current collector and a positive active layer disposed on at least one side surface of the positive current collector, the positive active layer including a positive active material; The positive electrode active material includes a positive electrode active material, or it includes a positive electrode active material and a coating layer disposed on the surface of the positive electrode active material.

10. The secondary battery according to claim 9, characterized in that, The positive electrode active material includes LiNi x Co y Mn z M a O2, where 0.8 ≤ x ≤ 0.95, 0.01 ≤ y ≤ 0.18, 0.01 ≤ z ≤ 0.18, 0 < a ≤ 0.1, and M includes at least one of Al, Mg, Y, W, B, Zr, Ti, Sr, La, and Nb; And / or, the coating layer comprises a metal oxide; And / or, the thickness of the coating layer is 10 nm to 50 nm; And / or, the positive electrode active material includes single crystal particles and / or polycrystalline particles; And / or, the particle size D50 of the positive electrode active material is 1 μm to 15 μm.

Citation Information

Cited By

  • Battery monomer, battery device and electric device

    CN121709625A

  • Battery cells, battery packs and electrical devices

    CN121709625B